2014
DOI: 10.4062/biomolther.2014.061
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits IL-6-Induced Transcriptional Activity of AR and STAT3 in Human Prostate Cancer LNCaP-FGC Cells

Abstract: Prostate cancer is the most frequently diagnosed cancer. Although prostate tumors respond to androgen ablation therapy at an early stage, they often acquire the potential of androgen-independent growth. Elevated transcriptional activity of androgen receptor (AR) and/or signal transducer and activator of transcription-3 (STAT3) contributes to the proliferation of prostate cancer cells. In the present study, we examined the effect of resveratrol, a phytoalexin present in grapes, on the reporter gene activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Resveratrol has been shown to reduce the levels of circulating androgen precursors, but it has no effect on testosterone, DHT, or prostate‐specific antigen (PSA) levels or prostate volume . Resveratrol also inhibits the dimerization of AR and the interleukin (IL)‐6–induced transcriptional activity of AR and STAT3 in human prostate cancer LNCaP‐FGC cells . Resveratrol treatment in AR + prostate cancer LNCaP cells induces a decrease in AR levels in a concentration‐dependent manner up to 150 μM .…”
Section: The Interactions Between Steroid Hormones and Resveratrolmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol has been shown to reduce the levels of circulating androgen precursors, but it has no effect on testosterone, DHT, or prostate‐specific antigen (PSA) levels or prostate volume . Resveratrol also inhibits the dimerization of AR and the interleukin (IL)‐6–induced transcriptional activity of AR and STAT3 in human prostate cancer LNCaP‐FGC cells . Resveratrol treatment in AR + prostate cancer LNCaP cells induces a decrease in AR levels in a concentration‐dependent manner up to 150 μM .…”
Section: The Interactions Between Steroid Hormones and Resveratrolmentioning
confidence: 99%
“…It prompts autophagy‐mediated cell death in PC3 and DU145 cells through the regulation of SOCE mechanisms, which include downregulation of STIM1 expression and triggering of endoplasmic reticulum stress by depleting endoplasmic reticulum calcium pools . Resveratrol inhibits STAT3 activation induced by IL‐6 and/or DHT, which induces AR transcriptional activity in LNCaP prostate cancer cells . In addition, resveratrol has been reported to inhibit hypoxia‐inducible factor‐1α (HIF‐1α)–mediated AR signaling and repress tumor progression in castration‐resistant prostate cancer .…”
Section: The Interactions Between Steroid Hormones and Resveratrolmentioning
confidence: 99%
“…It was found to target the AR axis in different in vitro and in vivo PCa models [47][48][49][50][51]. On one hand, in LNCaP cells it inhibited β-catenin nuclear translocation through hypoxia-inducible factor 1-α (HIF-1α) downregulation, thus suppressing β-catenin-mediated AR signaling [52]; similarly, it also repressed interleukin-6 (IL-6)-induced AR transcriptional activity [53]. On the other hand, in 22RV1 cells it promoted the AR splice variant ARV7 proteasomal degradation, by enhancing its polyubiquitination.…”
Section: Natural Compounds Modulating the Androgen Receptor Axismentioning
confidence: 99%
“…Dhar revealed that RSV downregulated metastasis associated protein 1 (MTA1), a PTEN inhibitor thereby causing inhibition of AKT pathway and hence controlling prostate cancer progression [145]. In LNCaP-FGC cells, when RSV treatment showed the inhibition of IL-6/DHT (Interlukin-6/dihydrotestosterone) induced androgen receptor (AR) transcriptional activity and partly mediated through suppression of STAT-3 reporter gene activity to hinder prostate cancer [146]. RSV along with other wine polyphenols showed anti-proliferative effects and induction of apoptosis in LNCaP cells via reduced expression of androgen receptor (AR) and caspase -3-7 [147].…”
Section: Resveratrol and Pancreatic Cancermentioning
confidence: 99%